Determination of Crop Co-efficient Values of Soybean (Glycine max [L.] Merrill) by Lysimeter Study (The Agriculturists, 2017)
Local level calibration of crop coefficient (Kc) values is critical for regional level planning and allocation of water resources for irrigation. In this regard, an experiment was conducted at the Irrigation and Water Management Division of Bangladesh Agricultural Research Institute (BARI), Gazipur, in order to estimate crop coefficient values of soybean under the local climatic condition. An improved crop variety- BARI Soybean-6 was used in this experiment. The crop was grown under four irrigation treatments, allowing irrigation at an interval of 10, 15, 20 and 25 days. The treatments were so designed that drainage was allowed between the consecutive irrigations. Irrigation at 15 days interval produced the highest seed yield of 1.26 t/ha and was considered to be suitable for estimating seasonal crop evapotranspiration (ETc) and Kc values. The seasonal highest cumulative ETc was 308.43 mm under this treatment. The Kc values of soybean at initial, development, mid-season and late season stages were found as 0.67, 1.46, 1.59 and 0.62, respectively.The Agriculturists 2016; 14(2) 14-23